Aspects of pain in sport - Pawlak, M. (Trends in Sport Sciences, 2013)
From a physiological point of view, pain in sport has an informative function, indicating the maximum load capacity of the body and especially of those areas which are usually exposed to maximum loads and, consequently, damage or injury. Pain in an athlete`s body usually has a specific cause, predictable duration, and proven methods of treatment. Pain is part of the sporting experience, irrespective of whether the discipline is a contact or a non-contact sport. Interest in the problems of pain in sport has been growing in recent years, as demonstrated by the host of scientific publications referred to in the paper, and in general the number of articles and studies available in thematic databases. The problem of pain in sport will become increasingly important, not least because of the increasingly higher load on athletes in all disciplines, as shown by the successive new world records. Also, the increasing number of amateur and recreational athletes will require appropriate studies. As this group is not sufficiently prepared for the effort, it is very susceptible to injury. Pain in sport can also be expected to continue to gain in importance considering the increasing number of active elderly people, especially in European countries. The article emphasizes that better knowledge of this area may have practical applications in the training process of athletes as well as persons who are physically active during their working life and after retirement. Furthermore, pain in sport may, due to advances in biological and medical sciences, give rise to new research areas. In this paper, the main trends of scientific problems and research concerning biological aspects of pain in sport are presented.From a physiological point of view, pain in sport has an informative function, indicating the maximum load capacity of the body and especially of those areas which are usually exposed to maximum loads and, consequently, damage or injury. Pain in an athlete`s body usually has a specific cause, predictable duration, and proven methods of treatment. Pain is part of the sporting experience, irrespective of whether the discipline is a contact or a non-contact sport. Interest in the problems of pain in sport has been growing in recent years, as demonstrated by the host of scientific publications referred to in the paper, and in general the number of articles and studies available in thematic databases. The problem of pain in sport will become increasingly important, not least because of the increasingly higher load on athletes in all disciplines, as shown by the successive new world records. Also, the increasing number of amateur and recreational athletes will require appropriate studies. As this group is not sufficiently prepared for the effort, it is very susceptible to injury. Pain in sport can also be expected to continue to gain in importance considering the increasing number of active elderly people, especially in European countries. The article emphasizes that better knowledge of this area may have practical applications in the training process of athletes as well as persons who are physically active during their working life and after retirement. Furthermore, pain in sport may, due to advances in biological and medical sciences, give rise to new research areas. In this paper, the main trends of scientific problems and research concerning biological aspects of pain in sport are presented.